Síntese de cumarinas, homoisoflavonoides e análogos bioativos - Ferreira, Alana Rodrigues (2023)
A set of twenty-four synthetic compounds comprising coumarin derivatives, homoisoflavonoids and analogues were prepared by different reaction methods, resulting in six new compounds. The structures of the synthetic products were characterized by infrared spectrometry, ¹H NMR and 13C NMR and high resolution mass spectrometry. Then, the compounds were evaluated for antifungal activity against Candida species, in vitro trypanocidal activity, and cytotoxic activity in human colon carcinoma (HCT-116) and human melanocyte (SK-MEL-28) cell lines. For the antifungal activity, the broth microdilution test was used to determine the Minimum Inhibitory Concentration (MIC) of the analogues and to verify the possible mechanism of antifungal action of the compounds with better bioactivity. The trypanocidal assay was carried out against the blood trypomastigote form of Trypanosoma cruzi, with determination of the IC50 of the compounds. The evaluation of cytotoxic activity was performed by the MTT test. In general, the evaluated compounds showed weak activity in reducing the cell viability of the strains used in the cytotoxic study. But promising results were obtained in antifungal action. Coumarin derivative 8 exhibited the best antifungal profile suggesting that the pentyloxy substituent at the C-7 position of coumarin may enhance this bioactivity. For a better understanding of its antifungal capacity 8 and 21 were submitted to a study of the mode of action on fungal membrane or cell wall. It was observed that the molecules do not interact directly with the ergosterol present in the plasma membrane or with the fungal cell wall, which suggests that their bioactivity is due to the action on other pharmacological targets. Compound 8 was also evaluated for its ability to inhibit the biofilm of C. tropicalis ATCC 13803. It promoted a statistically significant reduction of the biofilm at concentrations of 0.268 μmol/mL and 0.067 μmol/mL, when compared to the control group. Considering its antifungal profile, 8 was also subjected to a molecular modeling study, which suggested that its antifungal capacity occurs by interfering with the redox balance of the yeast cell and by compromising the synthesis of the plasmatic membrane, not through a direct interaction with its components, but by interfering with the synthesis of ergosterol. Another important finding was the antifungal capacity of homoisoflavonoids 23 and 24, derivative 23 showed slightly higher antifungal activity, possibly due to the presence of the methoxyl substituent in the meta position on ring B. In the study of trypanocidal activity, homoisoflavonoid derivative 23 showed the best bioactivity with IC50 = 0.0078 ± 0.0023 μmol/mL; LC50 = 0.0176 ± 0.0049 μmol/mL and SI = 2.3; the meta position of the -OCH3 substituent contributed to the antiparasitic action of 23. Thus, molecules 8 and 23 exhibited promising results in antifungal and trypanocidal activity, respectively. These results can be used in future research to obtain candidates with antifungal and antiparasitic activity, which are more potent and safe.